Integration of Renewable Energy and Electric Vehicles in Microgrid Systems: Performance Enhancement with 18MW Capacity and Unity Power Factor - Mr. R Venkatachalam; Mr. M Seenivasan; Dr. Velappagari Sekhar; Mr. V Pandiyan (Utilitas Mathematica, 2024)
The rapid adoption of Electric Vehicles (EVs) due to increasing environmental concerns and carbon emissions has significantly impacted modern power systems. As EV penetration rises, their integration with microgrids presents challenges related to grid stability, voltage regulation, and energy management. This study investigates the enhanced performance of a renewable energy-integrated microgrid with an upgraded capacity of 18 MW and a unity power factor, ensuring improved efficiency and reduced reactive power losses. The proposed microgrid consists of a diesel generator as the primary power source, supplemented by a Photovoltaic (PV) farm and a wind farm, which contribute to sustainable energy generation. Additionally, a Vehicle-to-Grid (V2G) system is deployed to optimize EV charging and discharging cycles, enhancing flexibility in energy distribution. The study focuses on the dynamic impact of EVs on microgrid performance, considering the nonlinear circuit characteristics of EV systems. Reliable charging infrastructure plays a crucial role in balancing grid loads, particularly in high-demand areas such as hospitals, universities, EV charging stations, and industrial sectors. Advanced control strategies are employed to regulate power flow and maintain voltage stability. The analysis is conducted using MATLAB/Simulink, providing a comprehensive assessment of how the upgraded microgrid, with 18MW capacity and unity power factor, improves operational efficiency, mitigates power fluctuations, and promotes sustainable energy solutions. This research highlights the critical role of renewable energy and EVs in enhancing microgrid performance and ensuring grid reliability.